Educational intervention: Self-care in Ostomised patients - Jiménez-Chunga, Elisa (2022)
Objective: To determine the level of knowledge before and after educational intervention on self-care in ostomized patients attending the Ostomal and Wound Therapy Unit at the National Institute of Neoplastic Diseases. Methodology: Quantitative study, pre-experimental longitudinal design. Population: a sample of 122 patients. A questionnaire was used on self-care knowledge in patients with the following dimensions: ostomy knowledge, ostomy management, feeding, ostomy complications, and products used for ostomy care. The results obtained in the pretest, 61.5% of patients know the ostomy, 60.7% have ostomy care, 31.1% have fed, and after the educational intervention, they achieved 100% knowledge. In the case of knowledge of complications and materials 18% and 23.0% were found, respectively, after the nursing educational intervention they obtained 96.7% of cognitive ability. Conclusions: The educational intervention should be permanent to guarantee the importance of the care given by the nurse of the service, empowering the nurse as an educator.